2015
DOI: 10.1037/per0000104
|View full text |Cite
|
Sign up to set email alerts
|

Explicit and inferred motives for nonsuicidal self-injurious acts and urges in borderline and avoidant personality disorders.

Abstract: Non-suicidal self-injury (NSSI) is a perplexing phenomenon that may have differing motives. The present study employed experience sampling methods (ESM) which inquired explicitly about the motives for NSSI, but also enabled a temporal examination of the antecedents/consequences of NSSI, these allowed us to infer other motives which were not explicitly endorsed. Adults (N=152, aged 18–65) with borderline personality disorder (BPD), avoidant personality disorder (APD), or no psychopathology participated in a 3-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
76
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 42 publications
9
76
1
Order By: Relevance
“…For example, studies demonstrate that both intensity (Armey et al, 2011;Berg et al, 2013;Engel et al, 2013;Haedt-Matt and Keel, 2011a;Smyth et al, 2007;Snir et al, 2015) and variability of negative affect (Anestis et al, 2012;Goldschmidt et al, 2014;Lavender et al, 2013;Vansteelandt et al, 2013) predict NSSI and DE. Moreover, studies show that NSSI and DE often occur in response to interpersonal stressors (Goldschmidt et al, 2014;Prinstein et al, 2009), and their associated negative emotions (e.g., feeling rejected or hurt; Nock et al, 2009;Snir et al, 2015), although behaviors themselves typically occur when people are alone (Nock et al, 2009). Micro-longitudinal studies have also investigated the role of food, hunger and weightrelated cues in predicting DE (Haedt-Matt and Keel, 2011b;Leahey et al, 2011;Zunker et al, 2011).…”
Section: Co-occurring Non-suicidal Self-injury and Disordered Eatingmentioning
confidence: 99%
“…For example, studies demonstrate that both intensity (Armey et al, 2011;Berg et al, 2013;Engel et al, 2013;Haedt-Matt and Keel, 2011a;Smyth et al, 2007;Snir et al, 2015) and variability of negative affect (Anestis et al, 2012;Goldschmidt et al, 2014;Lavender et al, 2013;Vansteelandt et al, 2013) predict NSSI and DE. Moreover, studies show that NSSI and DE often occur in response to interpersonal stressors (Goldschmidt et al, 2014;Prinstein et al, 2009), and their associated negative emotions (e.g., feeling rejected or hurt; Nock et al, 2009;Snir et al, 2015), although behaviors themselves typically occur when people are alone (Nock et al, 2009). Micro-longitudinal studies have also investigated the role of food, hunger and weightrelated cues in predicting DE (Haedt-Matt and Keel, 2011b;Leahey et al, 2011;Zunker et al, 2011).…”
Section: Co-occurring Non-suicidal Self-injury and Disordered Eatingmentioning
confidence: 99%
“…Finally, several studies have examined suicidal ideation, nonsuicidal self-injury (NSSI), and suicidal behavior . Findings indicate that: (a) negative mood intensity is related to suicidal ideation [14]; (b) we do not always see evidence for a negative reinforcement process from NSSI (i.e., a reduction in negative affect after NSSI) [15], and (c) motives for NSSI and suicidal behavior may vary across individuals and across occasions [15]. …”
Section: Review Of Aa Studies Of Bpdmentioning
confidence: 99%
“…Previous EMA studies have repeatedly addressed this question but have largely focused on only one specific BPD symptom and how it related to NA, whereas a broader picture of how NA relates to all nine symptoms of the BPD syndrome has rarely been addressed (see Law et al, 2016, for an exception). Previous EMA studies have revealed positive associations between NA and interpersonal problems (Berenson, Downey, Rafaeli, Coifman, & Leventhal Paquin, 2011;Hepp et al, 2017;Hepp, Lane, Wycoff, Carpenter, & Trull, 2018), impulsivity (Tomko et al, 2015) or impulsive behaviors such as drinking (Jahng et al, 2011), and NSSI (Andrewes et al, 2017;Houben et al, 2017;Scala et al, 2018;Snir, Rafaeli, Gadassi, Berenson, & Downey, 2015). Fewer studies have addressed NA in daily life in relation to the remaining symptoms of BPD.…”
mentioning
confidence: 99%